THE EFFECT OF WORK MOTIVATION AND WORK ENVIRONMENT ON EMPLOYEE PERFORMANCE AT PT PERKEBUNAN NUSANTARA IV REGIONAL II PKS SOSA UNIT - Aziz Karim Harahap; Purjianto (International Journal of Social Science, Educational, Economics, Agriculture Research and Technology (IJSET), 2026)
This study aims to determine the partial and simultaneous effects of work motivation and work environment on employee performance at PT Perkebunan Nusantara IV Regional II Unit PKS Sosa. This research is a quantitative study applying a survey method with structured questionnaires for data collection. The respondents involved were 58 male employees. Data analysis methods included validity and reliability tests, classical assumption tests, multiple linear regression analysis, and hypothesis testing (t-test and F-test) using SPSS version 23 software. The results showed that partially, work motivation had a significant effect on employee performance with a significance value of 0.018 < 0.05 (t-statistic 2.429). The work environment also significantly affected employeeperformance partially with a significance value of 0.006 < 0.05 (t-statistic 2.888). Simultaneously, work motivation and work environment had a significant effect on employee performance with a significance value of 0.000 < 0.05 (F-statistic 19.651). The coefficient of determination (R2) of 41.7% indicated that both independent variables could explain employee performance variants, while the remaining 58.3% was influenced by other variables outside this research model. Based on the partial test, the work environment was identified as the most dominant variable affecting employee performance at PKS Sosa due to its smaller significance value.